Food and Environmental Sustainability Nexus: A Key to Economic Development in Nigeria - Mgbemena , Emilia M.; Obi ., Cyril O.; Chinonye , Anne Maduka (African Journal of Education,Science and Technology (AJEST), 2014)
One of the most important challenges of man at all times has been to obtain enough food to meet not only the present demands of the family, but essentially its availability and accessibility at all times for a healthy life. The developmental policy goals in Nigeria among other things include: to ensure that the nation produces food to the extent that there is enough food per capita and at affordable prices and to reduce threats on the environment, the source of our natural capital. But it is certain that the quest for food security requires the continuous dependency on the environment. Soil degradation, soil erosion, deforestation and extinction of some animals are some of the consequences of this misuse of the environment. This paper underscores the importance of sustainable food productivity in Nigeria. This concern is not only born from the challenge of food security but also from the important link between sustainability in food production and environmental sustainability given the present global environmental challenges. The paper argues that it is possible to achieve sustainable food production that will also conserve the environment, that development of environmental friendly technologies and practices accessible to and effective for farmers will mitigate environmental depletion and also open up great economic opportunities. It further provides evidences for these claims. This paper therefore calls for an inward look again by mainstreaming sustainable agriculture at our national levels.